Durability characteristics of self-consolidating high strength concrete containing ground palm oil fuel ash as a partial cement replacement / Belal Gamal Muthanna Alsubari - Belal Gamal, Muthanna Alsubari (2015)
Palm oil fuel ash (POFA) is considered as a waste material, and it is dumped into landfills without any commercial return or cycling which considered as a costly practice. Previous studies have shown that POFA is a pozzolanic material and can be used as a partial cement replacement in concrete. However, there is a little information regarding the use of POFA as a cement replacement for producing self-consolidating high-strength concrete (SCHSC) as well as there is not any report in the case of durability properties of this type of concrete. In this study POFA has been used as a partial cement replacement to produce SCHSC. Samples were made by replacing Type I Portland cement with various proportions (0%, 10%, 15%, and 20%) of POFA. Fresh properties such as filling ability, passing ability, and segregation resistance were examined to fulfil the requirements of self-compacting concrete according to EFNARC standard. The hardened properties and durability characteristics, such as compressive strength, drying shrinkage strain, rapid chloride permeability, initial surface absorption, acid attack, sulphate attack, and water absorption tests have been studied. Test results showed that SCHSC integrated with POFA can be produced with no adverse effects on the fresh properties. Incorporating ground POFA caused a reduction in the drying shrinkage strain of all the mixes containing POFA compared to concrete made with OPC. SCHSC containing ground POFA showed a significant reduction in the initial surface absorption, and 20% cement replacement level with the POFA exhibited the lowest initial surface absorption compared to all mixes. Integration of ground POFA as a partial cement replacement increases the resistance of SCHSC towards rapid chloride permeability, acid attack, and sulphate attack. 20% cement replacement showed the highest resistant toward chemicals attack. Conclusively, incorporating POFA as a partial cement replacement in SCHSC does not cause adverse effects on the fresh properties and significantly improved durability characteristics of SCHSC concrete.